Erikson, Eskimos & Columbus : medieval European knowledge of America - Enterline, James Robert (Johns Hopkins University Press, 2002)
Why did medieval Europeans seem to have such specific knowledge about a land they had not yet discovered? The author presents evidence that the Eskimos' provided the basis for medieval maps of the areas of America that no Europeans had reached.